Determination of tectonic velocities of some continuously operating reference stations (CORS) in Vietnam 2016-2018 by using precise point positioning - Lau, Nguyen Ngoc; Coleman, Richard; Hoa, Ha Minh (Vietnam Journal of Earth Sciences, 2020)
Determining the speed of tectonic plate displacement helps us to better understand tectonic activities of the area, and is a prerequisite to help forecast earthquakes. The determination of tectonic plate displacement by GNSS technology in Vietnam has been conducted since the 2000s, mainly using the relative positioning technique. The increasing accuracy of precise point positioning technique, and the number of CORS in Vietnam, will facilitate the accurate determination of tectonic velocities. Based on the GNSS data of some CORSs in Vietnam from 2016-2018, we have determined accurately their three-dimensional coordinates using a precise point positioning technique. After modeling periodic variations on the time series, we calculated the tectonic movement rate of 7 Vietnamese stations and 3 other stations in the region. Through analysis and comparison with other geology/plate motion models and GPS results, we conclude that this result is reliable. The velocity of tectonic motion in the North, East and Up components of Ha Noi, Da Nang and Ho Chi Minh City are respectively (-13.1, +32.8, -1.3), (-9.9, +31.0, +2.6) and (-10.3, +26.9, +2.7) mm/year.